(3GdefgL GdeHjf aj TQM GdCQHYjfs - (3CHh MaU YeQ Hf Ydj GddNei GdeGdcj GdEScfOQis; (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s ((3CMeO Hf jhfS GdCSjhWi GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CXgQ GdSfI hCfGQgG CeG HYO aEfg bO cGf NWQ di Cf CLeY CQHYjf MOjKkG ef CMGOjKg Udi Gddg Ydjg hSde adeG hbaJ Ydi GdCQHYjf GdJi JQLgG eMi GdOjf Gdfhhi hLOJgG ef Cgde eG LeY ai Pdc P s
(3BNQgG (B:s
(3hgPG BNQ eG hab Gdgd JYGdi Edjg ef TQM gPg GdC;GOjK GdCQHYjf Ydi MSH GdEecGf hGdMeO ddg GdcQje GdefGf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs